Towards an educational philosophy promoting democracy and global citizenship - Jarrar, Amani Ghazi (Al-Adab Journal, 2019)
The study presents a vision of a democratic educational philosophy that promotes building a global citizen. The study uses the philosophical analysis method and the descriptive approach trying to understand and evaluate the educational curriculum, in order to propose a philosophical and educational vision that contributes to the creation and promotion of global citizenship. The study concluded that the adoption of the democratic model in education at various stages, including higher education helps in development of global citizens.